Cardiovascular protection by SGLT2 inhibitors - Do anti-inflammatory mechanisms play a role? - Asmaa Elrakaybi; Katharina Laubner; Qian Zhou; Martin J. Hug; Jochen Seufert (Elsevier, 2022)
Background: Metabolic syndrome and related metabolic disturbances represent a state of low-grade inflammation, which accelerates insulin resistance, type 2 diabetes (T2D) and cardiovascular disease (CVD) progression. Among antidiabetic medications, sodium glucose co-transporter (SGLT) 2 inhibitors are the only agents which showed remarkable reductions in heart failure (HF) hospitalizations and major cardiovascular endpoints (MACE) as well as renal endpoints regardless of diabetes status in large randomized clinical outcome trials (RCTs). Although the exact mechanisms underlying these benefits are yet to be established, growing evidence suggests that modulating inflammation by SGLT2 inhibitors may play a key role. Scope of review: In this manuscript, we summarize the current knowledge on anti-inflammatory effects of SGLT2 inhibitors as one of the mechanisms potentially mediating their cardiovascular (CV) benefits. We introduce the different metabolic and systemic actions mediated by these agents which could mitigate inflammation, and further present the signalling pathways potentially responsible for their proposed direct anti-inflammatory effects. We also discuss controversies surrounding some of these mechanisms. Major conclusions: SGLT2 inhibitors are promising anti-inflammatory agents by acting either indirectly via improving metabolism and reducing stress conditions or via direct modulation of inflammatory signalling pathways. These effects were achieved, to a great extent, in a glucose-independent manner which established their clinical use in HF patients with and without diabetes.